'A Beautiful Bridge': Chinese Indonesian Associations, Social Capital and Strategic Identification in a New Era of China–Indonesia Relations. Issue 102 (1st November 2016) - Setijadi, Charlotte
Abstract: In Indonesia, Chinese voluntary associations took on a new level of importance after the fall of Suharto's New Order regime in 1998 that ushered in a revival of Chinese identity politics. At the same time, Sino-Indonesian relations are blossoming, and the rise of China as a global power means that Indonesia can only benefit from stronger ties with China in the future. In this new atmosphere of cooperation, I argue that Chinese Indonesian individuals and voluntary organizations play a crucial function as trade and cultural intermediaries. Drawing on both empirical and qualitative fieldwork data, in this paper, I examine how members of Chinese voluntary organizations view their ethnicity, national belonging, and strategic position in the contexts of post-Suharto Chinese identity politics and Sino-Indonesia relations. More broadly, this paper also offers a critical analysis of the internal dynamics of contemporary Overseas Chinese voluntary organizations and the role they play in building trade and sociocultural relationships between China and other countries.